2019
DOI: 10.15446/dyna.v86n210.77450
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, physical and mechanical properties of kaolin–diatomite composite reinforced with CaCO3•

Abstract: The present work reports the microstructure, physical and mechanical properties of a material composed of kaolin, diatomite and calcium carbonate reinforcement (CaCO3). The ceramic prototypes were shaped by the slip casting method and sintered at temperatures between 800 °C and 1100 °C. The morphology and average pore size was analyzed by Scanning Electron Microscopy (SEM) and the mineralogical phases were determined by X-Ray Diffraction (XRD). The apparent density was established by the mercury immersion meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…On the other hand, Figure 4(b) exhibits MK morphology with dominantly plate-like particles of irregular shape, matching with studies previously reported (Fonseca-Páez et al, 2019;Ríos et al, 2009;Youssef et al, 2008).…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, Figure 4(b) exhibits MK morphology with dominantly plate-like particles of irregular shape, matching with studies previously reported (Fonseca-Páez et al, 2019;Ríos et al, 2009;Youssef et al, 2008).…”
Section: Resultssupporting
confidence: 90%